-x-6=34+3x

Simple and best practice solution for -x-6=34+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-6=34+3x equation:



-x-6=34+3x
We move all terms to the left:
-x-6-(34+3x)=0
We add all the numbers together, and all the variables
-x-(3x+34)-6=0
We add all the numbers together, and all the variables
-1x-(3x+34)-6=0
We get rid of parentheses
-1x-3x-34-6=0
We add all the numbers together, and all the variables
-4x-40=0
We move all terms containing x to the left, all other terms to the right
-4x=40
x=40/-4
x=-10

See similar equations:

| 9b-3=3(3b-1 | | -2x-6=-5x-6 | | 2+2x=44 | | -8+3x=5x-14 | | x-1=-5-x | | 5+3x=47 | | -31-4x=-5-5(1+5x)* | | 5( | | -5(c-89)=-25 | | 6x+3=-42+x | | 3x+7=-11+5x | | 5(j-83)=45 | | 4+2x=-x-26 | | 10+2y+y+5=180 | | -4x-7+10x=-7+6x* | | 12+4c=28 | | -3x+9=-7+5x | | 17+7x=45 | | x(5-0.2x)=0 | | -x+5=5+x | | 8(h-88)=24 | | 75+69=m∠2 | | (4+2i)+(-3-5i)=1-3i | | 14+1x=49 | | x+5=-4x+50 | | 15-3x+2=3+7x-2 | | 110400/x=16 | | 70.2=-6.9c+90.9 | | s-78/5=3 | | x+x(0.15)=30 | | 5(t+1)-3=17 | | -4(w-63)=-92 |

Equations solver categories